Cognitive and behavioral techniques used by olympic and paralympic swimmers to manage sport related thoughts and emotions - Valadao Saint Martin, Samira (2018)
The present study investigated the thoughts and emotions of swimmers and what techniques they used to manage them before and during their best and worst performances. Twelve male Brazilian swimmers (5 Olympic and 7 Paralympic) took part of the study. They were 22 to 37 years old (M = 26.16, SD = 4.32). Three athletes (25%) were middle distance swimmers in freestyle, and the other nine (75%) were sprinters in all four swimming styles. An in-depth semi-structured interview was designed to explore the internal processes of participants and the techniques they used to manage them in the competitive events. The interview consisted of three sections: the first section examined the thoughts and emotions related to the best performance and the techniques used to manage them. The second section focused on thoughts and emotions in the worst performance and the techniques used. The third section investigated athletes’ awareness about internal processes and the influence on performance. Interview data were inductively and deductively analyzed, based on emerging themes and concepts of cognitive behavior therapy (Beck, 1995). Imagery, breathing, self-talk, music, cognitive restructuring and motivational audios were the techniques used by swimmers to manage their thoughts and emotions. The techniques were mostly used before best performances than before worst performances. There was a great variability in how the techniques were utilized, regarding the purpose and timing before and on the day of the races. Although some of the athletes were already familiar with some of the techniques, they reported improvement in how and why to use them after started a psychological preparation with a sport psychologist. Athletes also mentioned that some techniques were not efficient, because the dysfunctional thoughts were constants in the worst performances. Functional thoughts and pleasant emotions were more common in the best performances, whereas dysfunctional thoughts and unpleasant emotions were more common in the worst ones. The swimmers believed that thoughts generate emotions and they can influence performance. However, only a few of them mentioned to be aware of how to manage this relationship to be more functional. Thus, it seems important to educate athletes to distinguish thoughts from emotions, how to identify and evaluate them, to have a functional behavior.